(untitled) (ACME, 2021)
Taking its cue from the work of John Tzetzes (1110-1185 ca), this paper offers a preliminary survey of the role played by bureaucratic and legal training in defining autography and authorship in 12th-century Byzantium. By comparing archival practices and authorial signatures, it demonstrates that features belonging to the legal discourse could be exploited by intellectuals to reinforce and re-center their voices as well as to overcome social constraints and, at time, marginality. The paper also takes a comparative perspective, by looking at the developments of vernacular poetry in Bologna, Tuscany and Sicily between 13th and 14th century, with a focus on the work of Francesco da Barberino. The comparative stance aims to prove that entanglements between legal/bureaucratic and literary writing are a cross-cultural constant emerging due to similar educational and scribal practices, thus showing that the case of the Italian pre-humanist intellectuals is the rule rather than the exception.